Evaluación de la aplicación de la norma legal tributaria en el cálculo del anticipo del impuesto a la renta - Polo Zhunio, Gissell Fernanda (2015)
In the present investigation has as main objective develop a model that allows for the calculation of the advance payment of income tax through a office tool based on the legal standard. The fundamental pillar is based on the theme of the origins of the direct tax and progressive in Latin America as Jose Pinto points out the income tax is a progressive tax, which is levied on the income of taxpayers, i.e. as it grows the economic capacity grows the percentage of its wealth that the State requires in the form of taxes; therefore the one who has a higher income should pay more taxes. The work is carried out under the modality of documentary research bibliography, which is based on the source of scientific articles, magazines, among others; for the quality of information that offers based on proven studies. For the advancement of the present investigation, has been taken as election the qualitative methodology by harvesting techniques that this offers to collect all the necessary information be of great support for the development of the work. The results obtained in the analysis of the calculation of the advance through the office tool showed that there was an error in the calculation, resulting in a difference in advance. It is recommended that you use the office tool that involves the handling of a template based on the implementation of the Tax Law, it is also recommended the use of the skills in tax matters, which will be of great help to reinforce knowledge.